MUSICAL WORK AS A SUBJECT OF AESTHETIC ANALYSIS IN THE WORKS OF R. INGARDEN - T.P. Reshetnikova; T.D. Furdak (Academy of Cognitive and Natural Sciences, 2022)
In this article the analysis of musical work its peculiarities of performance and perception in R. Ingard's monography (polish philosopher) is considered.